Tomorrow's doctors and today's changes: neo-liberal discourses and the daily practices of medical interns at a state university hospital in Cairo - Shokralla, Salma (AUC Knowledge Fountain, 2010)
As the State shifts towards liberalization policies in the health sector, debates surrounding the outcomes of medical encounters came to the core of public debate. To understand changes that are influencing medical encounters and their outcomes, this study focused on the socialization process medical students go through to become practicing physicians. A public university hospital (Al Kasr Al Ainy) where medical students get their practical training was the focus of this study. Courses on physician-patient encounters, newly implemented under the government's education reform plan, were analyzed as an example of how discourses are produced to shift the responsibility of public health from being a state responsibility to becoming an individualized one.